BigBovid- Evaluation of a Newly Developed 9 mm Bullet-Shooting Stunner for Adequate Stunning of Heavy Cattle - Gascho, Dominic; Stephan, Roger; Bauer, Clemens; Oesch, Michelle Aimée; Richter, Henning (Frontiers in Veterinary Science, 2022)
The stunning of heavy cattle and water buffalo is an animal welfare problem, as conventional cartridge fired captive-bolt stunners are not suitable due to the thicker skull bones and the greater depth of penetration required to reach and damage the relevant brain regions for deep unconsciousness. This current animal welfare problem requires a suitable and feasible as well as commercially available and legally approved stunning device to ensure deep unconsciousness of these animals. In this study, the use of a newly developed bullet-shooting stunner, the BigBovid, with two different types of hunting ammunition, namely .38 SPL FMJ-TC and .357 MAG FTX® bullets, was evaluated on twenty-two heavy cattle (mean weight: 1062.27 kg, standard deviation: 124.09 kg). In ballistic experiments, the BigBovid reached a mean energy density of 11.74 J/mm2 (SD: 0.12 J/mm2) for the .38 SPL FMJ-TC and 17.56 J/mm2 (SD: 0.52 J/mm2) for the .357 MAG FTX®. In in vivo experiments, the use of the .38 SPL FMJ-TC resulted in overpenetration four times. The .357 MAG FTX® bullets showed to be more advantageous, because on the one hand no overpenetration occurred and on the other hand the bullets fragmented into small parts after penetration into the skull. The fragments were scattered in the brain tissue, such as the thalamus and the brain stem, and thus there is a high probability to damage the brain regions relevant for deep unconsciousness. Based on the results of this study, the use of the BigBovid in combination with the .357 MAG FTX® bullet is found to be suitable for stunning heavy cattle.